Workplace Ostracism and Counterproductive Work Behaviors: The Chain Mediating Role of Anger and Turnover Intention - Zhu, Yingge; Zhang, Denghao (Frontiers in Psychology, 2021)
This study aims to explore the mediating effect of anger and turnover intention on the relationship between workplace ostracism and counterproductive work behaviors. A two-stage follow-up survey of 426 employees born after 1990 was conducted using the Workplace Ostracism Scale, Counterproductive Work Behaviors Scale, Trait Anger subscale of the State-Trait Anger Expression Inventory, and Turnover Intention Scale. Workplace ostracism was found to be significantly positively correlated with anger, turnover intention, and counterproductive work behaviors. Furthermore, anger and turnover intention both separately and serially mediated the relationship between workplace ostracism and counterproductive work behaviors. This study confirms the chain mediating effect of anger and turnover intention on the relationship between workplace ostracism and counterproductive work behaviors.